Mental health issues in adolescent mothers and young adult mothers: the Brazilian context - Amanda Ferreira de Carvalho; Daniela Dal Forno Kinalski Guaranha; Bruna Marmett; Júlia Mathias Reis; Carmem Lisiane Escouto de Souza; Bruna Silveira da Rosa; Tiago Chagas Dalcin; Sérgio Luis Amantea (Jornal de Pediatria, 2025)
Objective: To analyze anxiety and depression levels in adolescent and young adult mothers. Methods: This multicenter cross-sectional study was conducted across Brazil’s five regions. A non-probabilistic sample of 1177 adolescent (10–19 years) and young adult (20–29 years) mothers was selected proportionally based on regional live birth rates. Data collection (August 2022–May 2023) involved a structured questionnaire assessing mental health (DASS-21), family support, and quality of life. Statistical analyses were performed using RStudio©, with p-values < 0.05 considered significant. The study was approved by the Research Ethics Committee (CAAE: 55465822.0.2003.5086). Results: Depression or anxiety was reported by 22.7 % of both adolescent and young adult mothers, with 7.55 % and 7.07 % diagnosed during pregnancy, respectively. Among affected adolescents, 66.67 % did not seek follow-up care, primarily due to limited healthcare access (29.55 %). Adolescent mothers showed a higher prevalence of depression (p < 0.001), anxiety (p < 0.001), and stress (p = 0.027) postpartum. Depression was associated with a lack of emotional support from the child’s father (p = 0.096), insufficient family caregiving support (p = 0.014), and low perceived quality of life. Conclusion: Adolescent mothers exhibit greater vulnerability to mental disorders, emphasizing the need for targeted psychological and social support during the perinatal period.